Changes of immunological biomarkers in pediatric patients with seasonal allergic rhinitis - V.V. Shcherbak; T.O. Kryuchko; L.M. Bubyr; O.V. Izmailova; O.A. Poda (Zaslavsky O.Yu., 2023)
Background. Seasonal allergic rhinitis shows a constant upward trend not only among the adults but also in the children's population. A significant percentage of patients have a moderate and severe course of the disease, which leads to a significant deterioration in their quality of life. Since the pathogenesis of allergic rhinitis is represented by a complex cascade of immunological reactions involving a number of cytokines that play a role in the development of allergic inflammation of the upper respiratory tract, the priority direction of our work was an in-depth study of the pathogenetic mechanisms of this disease. The purpose was to investigate the levels of interleukin-33 (IL-33) and its suppression of tumorigenicity 2 (ST2) receptor in the blood serum of children with hay fever, depending on the age and severity of the disease, followed by the determination of correlations of these indicators with various clinical and immunological parameters of seasonal allergic rhinitis. Materials and methods. Forty-two patients aged 6-17 years with seasonal allergic rhinitis and 26 healthy children (controls) took part in the study. Severity of nasal and extra-nasal symptoms of allergic rhinitis was determined using a visual analog scale. Skin prick testing was performed according to generally accepted standards during remission using a standard pollen panel. Quantitative measurement of serum indicators of interleukin-33 and ST2 was carried out by the method of solid-phase enzyme immunoassay. A mandatory condition for conducting the study was the presence of written informed consent from the parents. Results. The study of serum levels of IL-33 and ST2 showed statistically higher concentrations in the group of children with a severe course of seasonal allergic rhinitis, a direct correlation of medium strength between content of the above cytokines in children with a mild SAR (τ = 0.65; p < 0.05) and a strong dependence in patients with moderate (τ = 0.76; p < 0.01) and severe (τ = 0.80; p < 0.05) course. When comparing the mean values of IL-33 and ST2, no significant changes were found depending on age and the presence of mono- or polysensitisation among patients with allergic rhinitis. In children with seasonal allergic rhinitis and concomitant bronchial asthma, there was a statistically significant tendency towards a more severe course of the disease with correspondingly higher values of IL-33 and ST2 compared to patients with isolated seasonal allergic rhinitis. Conclusions. The obtained results of the immunological study made it possible to emphasize the diagnostic significance of IL-33 and its receptor ST2 as potential biomarkers in the development of allergic inflammation in pediatric patients with seasonal manifestations of rhinitis.